2021
DOI: 10.3390/molecules26154409
|View full text |Cite
|
Sign up to set email alerts
|

Gomisin M2 Ameliorates Atopic Dermatitis-like Skin Lesions via Inhibition of STAT1 and NF-κB Activation in 2,4-Dinitrochlorobenzene/Dermatophagoides farinae Extract-Induced BALB/c Mice

Abstract: The extracts of Schisandra chinensis (Turcz.) Baill. (Schisandraceae) have various therapeutic effects, including inflammation and allergy. In this study, gomisin M2 (GM2) was isolated from S. chinensis and its beneficial effects were assessed against atopic dermatitis (AD). We evaluated the therapeutic effects of GM2 on 2,4-dinitrochlorobenzene (DNCB) and Dermatophagoides farinae extract (DFE)-induced AD-like skin lesions with BALB/c mice ears and within the tumor necrosis factor (TNF)-α and interferon (IFN)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…By suppressing the activation of keratinocytes, the major epidermal cells actively involved in AD HDMs are the unsurpassed cause of allergic diseases such as AD, asthma, and rhinitis throughout the world, and Dermatophagoides farinae used in the experiment is the major species of HDM [8]. Based on the previous studies, DNCB was used as a hapten for pre-sensitization, and DFE was used as an allergen to induce AD-like skin inflammation in this study [44,45]. Repeated applications of DNCB/DFE showed common phenotypes of AD, including erythema, scaling, hyperplasia, thickened skin as well as infiltration of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…By suppressing the activation of keratinocytes, the major epidermal cells actively involved in AD HDMs are the unsurpassed cause of allergic diseases such as AD, asthma, and rhinitis throughout the world, and Dermatophagoides farinae used in the experiment is the major species of HDM [8]. Based on the previous studies, DNCB was used as a hapten for pre-sensitization, and DFE was used as an allergen to induce AD-like skin inflammation in this study [44,45]. Repeated applications of DNCB/DFE showed common phenotypes of AD, including erythema, scaling, hyperplasia, thickened skin as well as infiltration of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, α-cubebenoate and gomisin M2 isolated from S. chinensis prevented eosinophil and mast cell infiltration in AD mice and prevented antigen-induced degranulation in RBL-2H3 cells [ 8 , 9 ]. These results suggest that the effect of suppressing immune cell infiltration of S. chinensis can be explained by the above components.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that S. chinensis contains ingredients with antioxidant effects, so it has a skin-whitening effect and suppresses skin irritation [ 2 , 3 ]. In addition, S. chinensis has been reported to have anti-oxidative [ 2 ], anti-aging [ 4 ], anti-allergic [ 5 ], and anti-inflammatory [ 6 ] effects, and the two primary components of S. chinensis , α-cubebenoate and gomisin M2, have been found to have anti-inflammatory effects in mice with experimental AD [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DNCB increases the expression of various cytokines and chemokines that cause AD [ 40 , 41 ]. The skin lesions of chronic AD have many characteristics, such as dryness, epidermis and dermis thickness, and lichenification, and AD induces various responses within the immune system, affecting the weight of immune organs such as the spleen [ 42 , 43 ]. We demonstrated that PLG reduced the severity of lesions on mice skin, epidermal and dermal thickening, and spleen weight, and demonstrated that PLG suppressed immune responses and improved histological characteristics.…”
Section: Discussionmentioning
confidence: 99%